Towards a national PID strategy - Brown, C (Bodleian Libraries, University of Oxford, 2023)
Persistent identifiers are already part of the Scholarly Communications and Research information landscape, helping to identify researchers (ORCID) and research outputs (DOI). These have proved valuable for enabling online referencing and citation, as well as improving and automating some administrative processes (e.g Symplectic). However, ORCIDs and DOIs can only get us so far, and further reductions in administrative overheads through automation require the adoption of additional identifiers. This presentation will provide up update on work that is happening at a national level in this area.